2015
DOI: 10.1039/c5cc00926j
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic water oxidation by CuII complexes with branched peptides

Abstract: Two mononuclear Cu II complexes with tetrapeptides incorporating a L-2,3-diaminopropionic acid (dap) branching unit are reported to undergo PCET and catalyse water oxidation. C-terminal His extension of dap (L = 2GH) instead of Gly (L = 3G) lowers the pK a for Cu III H À2 L (9.36 vs. 9.98) and improves the TOF at pH 11 (53 vs. 24 s À1 ).Reactions requiring the synchronous transfer of multiple protons and electrons become energetically viable under mild conditions through the catalytic promotion of proton-coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 21 publications
2
76
0
Order By: Relevance
“…The group proposed a plausible catalytic cycle of 17, which is similar to the well-known catalytic cycle of mononuclear copper-based water oxidation catalysts 3 (Figure 8) , from which dioxygen is liberated to close the catalytic cycle. Similar copper-based catalysts housing a polypeptide ligand were also reported by Pap and Szyrwiel et al 37 Although several copper-based water oxidation catalysts have been developed, all catalysts mentioned above require alkaline conditions to drive the water oxidation reaction. Zhang et al first reported a copper-based catalyst that operates at a neutral pH.…”
Section: ¹1supporting
confidence: 63%
“…The group proposed a plausible catalytic cycle of 17, which is similar to the well-known catalytic cycle of mononuclear copper-based water oxidation catalysts 3 (Figure 8) , from which dioxygen is liberated to close the catalytic cycle. Similar copper-based catalysts housing a polypeptide ligand were also reported by Pap and Szyrwiel et al 37 Although several copper-based water oxidation catalysts have been developed, all catalysts mentioned above require alkaline conditions to drive the water oxidation reaction. Zhang et al first reported a copper-based catalyst that operates at a neutral pH.…”
Section: ¹1supporting
confidence: 63%
“…1 top and an I2M mechanism is found when the favored species resemble those of the oxyl radical form depicted in the lower part of Figure 1 Recently several first row transition metal complexes have been reported as catalysts for the water oxidation reaction. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] While these catalysts are of interest because of their high abundance and low toxicity, their performance is much poorer than their Ru or Ir analogues, and in addition their mechanistic pathways are in most cases basically unknown. [28][29][30][41][42][43] We have very recently reported a new complex based on Cu, containing the amidate ligand OPBAN that can carry out the water oxidation reaction in a very efficient manner.…”
Section: Introductionmentioning
confidence: 99%
“…6) Instead of CV we applied square-wave voltammetry (SWV) to determine the E 0 values accurately, upon shiing the pH by small increments. 1 The E net (potential of I net ) vs. pH plots will directly give Pourbaix diagrams, when reversibility terms of the (Table S1 sums the data, Fig. S4 † illustrates reproducibility).…”
Section: Electrochemistrymentioning
confidence: 99%
“…is the formal potential of the process in eqn (1). Fit of eqn (2) to E net data points yields the line in Fig.…”
mentioning
confidence: 99%